RECURRING CYSTOLITHIASIS IN MALE CATS - Pratama, I Made Kerta; Erawan, I Gusti Made Krisna; Widyastuti, Sri Kayati (Buletin Veteriner Udayana, 2023)
Cystolithiasis is a condition where uroliths/calculi are found in the urinary bladder (VU) caused by multifactorial factors, namely urine pH, feed, and bacterial infection. An orange mixed breed cat, male, four years old, weighing 5.2 kg was examined at the Prema Veterinary Clinic, Dalung, Bali, with complaints of not urinating for 5 days, weakness, and decreased appetite. A case cat was reported to have come to the clinic in January with the same complaint. examination Ultrasound showed thickening of the walls of the VU and crystals were found in the VU. Animal cases were treated with catheterization, fluid therapy with Ringer's Lactate , ciprofloxacin (10 mg/kg BW; q24h), phenylpropanolamine HCL (0.8 mg/kg BW; q8h), vitamin Hematodine (0.6 mL) and case cats were also given. Neurotropic vitamins ® (0.6 mL) and given cat food royal canine urinary care . One week after therapy the cat is in good condition, urinating smoothly and there is no indication of pain when urinating